Carcinoid tumour of male breast diagnosed by fine needle aspiration. - Schmitt, F. C.; Brandão, M. (Wiley, 1990)
A primary carcinoid tumour of the breast in a 66-year-old man was diagnosed by fine-needle aspiration cytology. The nature of the lesion was proved by histochemical and immunocytochemical studies. The importance of a conclusive diagnosis is discussed and the value of immunocytochemical analysis as an aid to cytomorphologic diagnosis is demonstrated.
Keywords: enolase; keratin; tumor marker; tumor protein; aged; breast tumor; carcinoid; case report; cell granule; chemistry; human; male; needle biopsy; pathology; Aged; Biopsy, Needle; Breast Neoplasms; Carcinoid Tumor; Case Report; Cytoplasmic Granules; Human; Keratin; Male; Neoplasm Proteins; Phosphopyruvate Hydratase; Tumor Markers, Biological